Catalytic Hydrogenation of Levulinic Acid in Water into g-Valerolactone over Bulk Structure of Inexpensive Intermetallic Ni-Sn Alloy Catalysts - Rodiansono Rodiansono; Maria Dewi Astuti; Abdul Ghofur; Kiky C. Sembiring (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
A bulk structure of inexpensive intermetallic nickel-tin (Ni-Sn) alloys catalysts demonstrated highly selective in the hydrogenation of levulinic acid in water into g-valerolactone. The intermetallic Ni-Sn catalysts were synthesized via a very simple thermochemical method from non-organometallic precursor at low temperature followed by hydrogen treatment at 673 K for 90 min. The molar ratio of nickel salt and tin salt was varied to obtain the corresponding Ni/Sn ratio of 4.0, 3.0, 2.0, 1.5, and 0.75. The formation of Ni-Sn alloy species was mainly depended on the composition and temperature of H2 treatment. Intermetallics Ni-Sn that contain Ni3Sn, Ni3Sn2, and Ni3Sn4 alloy phases are known to be effective heterogeneous catalysts for levulinic acid hydrogenation giving very excellence g-valerolactone yield of >99% at 433 K, initial H2 pressure of 4.0 MPa within 6 h. The effective hydrogenation was obtained in H2O without the formation of by-product. Intermetallic Ni-Sn(1.5) that contains Ni3Sn2 alloy species demonstrated very stable and reusable catalyst without any significant loss of its selectivity. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)